A Recombinant Rift Valley Fever Virus Glycoprotein Subunit Vaccine Confers Full Protection against Rift Valley Fever Challenge in Sheep - Faburay, Bonto; Wilson, William C.; Gaudreault, Natasha N.; Davis, A. S.; Shivanna, Vinay; Bawa, Bhupinder; Sunwoo, Sun Young; Ma, Wenjun; Drolet, B. S.; Morozov, I.; McVey, D. S.; Richt, Juergen A. (My University, 2016)
Rift Valley fever virus (RVFV) is a mosquito-borne zoonotic pathogen causing disease outbreaks in Africa and the Arabian Peninsula. The virus has great potential for transboundary spread due to the presence of competent vectors in non-endemic areas. There is currently no fully licensed vaccine suitable for use in livestock or humans outside endemic areas. Here we report the evaluation of the efficacy of a recombinant subunit vaccine based on the RVFV Gn and Gc glycoproteins. In a previous study, the vaccine elicited strong virus neutralizing antibody responses in sheep and was DIVA (differentiating naturally infected from vaccinated animals) compatible. In the current efficacy study, a group of sheep (n=5) was vaccinated subcutaneously with the glycoprotein-based subunit vaccine candidate and then subjected to heterologous challenge with the virulent Kenya-128B-15 RVFV strain. The vaccine elicited high virus neutralizing antibody titers and conferred complete protection in all vaccinated sheep, as evidenced by prevention of viremia, fever and absence of RVFV-associated histopathological lesions. We conclude that the subunit vaccine platform represents a promising strategy for the prevention and control of RVFV infections in susceptible hosts.
Citation: Faburay, B., Wilson, W. C., Gaudreault, N. N., Davis, A. S., Shivanna, V., Bawa, B., . . . Richt, J. A. (2016). A Recombinant Rift Valley Fever Virus Glycoprotein Subunit Vaccine Confers Full Protection against Rift Valley Fever Challenge in Sheep. Scientific Reports, 6, 12. doi:10.1038/srep27719
Keywords: Monoclonal-Antibodies; Immune-Responses; Efficacy; Safety; Expression; Strain